Locating Civil Society’s Anti-Corruption Role Through Configurational Analysis: Towards A Policy and Research Agenda - Villanueva, Prince Aian G. (HAPSc Policy Briefs Series, 2022)
While corruption studies abound, there is a dearth of scholarship that deals with corruption from the perspective of set relations. A configurational analysis of corruption is helpful in understanding the complexity of such phenomenon. For one, given the complex nature of corruption, democratic governments and civil society are prompted to address it via holistic and integrative anti-corruption strategies. This complexity seems to resonate with what qualitative comparative analysts hold regarding the import of contexts and with the configurational character of much of social life. From the perspective of set-theoretic, configurational analysis, in particular qualitative comparative analysis (QCA), corruption should also thus be seen as a conjunctural, equifinal, asymmetrical, and multifinal phenomenon.